Mitochondrial dysfunction in Trypanosoma cruzi: the role of Serratia marcescens prodigiosin in the alternative treatment of Chagas disease (2011)
ABSTRACT: Background: Chagas disease is a health threat for many people, mostly those living in Latin America. One of the most important problems in treatment is the limitation of existing drugs. Prodigiosin, produced by Serratia marcescens (Rhodnius prolixus endosymbiont), belongs to the red-pigmented bacterial prodiginine family, which displays numerous biological activities, including antibacterial, antifungal, antiprotozoal, antimalarial, immunosuppressive, and anticancer properties. Here we describe its effects on Trypanosoma cruzi mitochondria belonging to Tc I and Tc II. Results: Parasites exposed to prodigiosin altered the mitochondrial function and oxidative phosphorylation could not have a normal course, probably by inhibition of complex III. Prodigiosin did not produce cytotoxic effects in lymphocytes and Vero cells and has better effects than benznidazole. Our data suggest that the action of prodigiosin on the parasites is mediated by mitochondrial structural and functional disruptions that could lead the parasites to an apoptotic-like cell death process. Conclusions: Here, we propose a potentially useful trypanocidal agent derived from knowledge of an important aspect of the natural life cycle of the parasite: the vector-parasite interaction. Our results indicate that prodigiosin could be a good candidate for the treatment of Chagas disease.